PERAN PEMERINTAH DALAM MENINGKATKAN KESEJAHTERAAN SOSIAL ANAK TERLANTAR MELALUI PROGRAM PERMAKANAN - Farida Sartika; Nanang Juhandi Hermawan; Maria Ulfah Awaliyah Suryana (PT. ABIG RIZKY PUBLISHER, 2026)
This study aims to analyze the role of the government in improving the social welfare of neglected children through the food assistance program in Cianjur Regency. The issue of neglected children, as part of the Social Welfare Problems (PMKS) category, remains a critical concern at the local level, particularly in fulfilling basic needs such as food and nutrition. This research employs a descriptive qualitative approach, with data collection techniques including in-depth interviews, observation, and documentation. Informants were selected using purposive sampling, involving officials from the Social Affairs Office and managers of Social Welfare Institutions (LKS). Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation. The results indicate that the government’s role has been relatively effective, as reflected in three main indicators: facilitator, regulator, and catalyst. The government has provided food assistance as a means of fulfilling basic needs, established regulations supporting program implementation, and promoted the improvement of social welfare among neglected children. However, several challenges remain, including uneven distribution of assistance, limited institutional guidance for LKS, and insufficient human resources with adequate information technology skills. Therefore, strengthening policy frameworks, enhancing institutional capacity, and optimizing the distribution system are necessary to ensure that the program operates more effectively and sustainably.